Can the state influence FDI regional distribution - The case of Czech Republic, Hungary, Poland and Serbia - Makojevic, Nikola; Kostic, Milan; Puric, Jelena (Industrija, 2016)
Using the data on foreign direct investment during transition in Czech Republic, Hungary, Poland and Serbia, we have examined the influence of government support programs for FDI equal distribution across those countries. The foreign direct investments tend to concentrate in regions where they can find adequate infrastructure and resources, thus widening the gap between developed and underdeveloped regions within a single economy. The governments of the observed countries have introduced support programs promoting equal FDI distribution across regions. We have analyzed the complete sample of FDI, registered within the observed period. The research shows a strong concentration of FDI in regions of capital cities in Hungary, Czech Republic and Serbia, while FDI distribution in Poland showed decreasing concentration during the observed period.